PENYELESAIAN SENGKETA TAMBANG: STUDI KASUS SENGKETA ANTARA MASYARAKAT SAMAWADENGAN PT. NEWMONT NUSA TENGGARA - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Exploration activity in Batu Hijau and Elang Dodo has been conducted since contract of work was settled between PT. Newmont Nusa Tenggara and government of Indonesia. In practical level, dispute arose out between local people of Samaw a ethnicity and the government Indonesia against PT. Newmont Nusa Tenggara. Research show, that the causing factors for the dispute are, among other things, the unresolved compensation, worliforce issue, and an unexpected their party intervening into the contract. The society wishes to resolve this dispute through adat law by negotiating or mediating with adat leaders as the mediator.